GC-MS Analysis of Bioactive Constituents of Hibiscus Flower - Rassem, Hesham H. A.; Nour, A. H.; R. M., Yunus (AENSI Publishing, 2017)
GC-MS the best technique to identified the compounds of essential oils by comparison of mass spectra data obtained from the sample with that taken from pure commercially available standards injected under the same conditions. Objective: To characterize the chemical constituents of Hibiscus Flower using GC-MS. The shade dried flower powder was extracted with methanol by using Microwave-assisted Hydrodistillation (MAHD). The Agilent 5975C Series GC/MS and a DB-WAX fused silica column (30 m x 0.25 mm i.d., film thickness 0.25 μm). Oven temperature was programmed to 60 0C for 10 min, and then increased at 200C/min to 2300C and held at 2500C for 10 min. The carrier gas, helium, was adjusted to a linear velocity of 30 cm/s. The GC-MS analysis provided different peaks determining the presence of fifteen compounds. These compounds have biological activity namely Ethanimidic acid, ethyl ester (31.43%), Propanal, 2,3-dihydroxy (12.58%), 4H-Pyran-4-one, 2,3-dihydro-3,5-di hydroxy-6-methyl (10.69%), Ethylenediamine (6.71%), o-Methylisourea hydrogen sulfate (4.06%), Ethene, ethoxy- (3.63%), Methyl palmitate (2.99%), 7-Formylbicyclo[4.1.0]heptanes (2.80%), 2-Butanamine, (S)- (2.72%), 1,3,5-Triazine-2,4,6-triamine (2.48%), N-Formyl-β-alanine (2.36%), (Z)6,(Z)9-Pentadecadien-1-ol (1.70%), 1,2-Ethanediamine, Butanedial (1.65%), N-methyl-1-Propanol, 2-methyl- (1.57%) and Methanecarbothiolic acid (1.08%). From the results, it can be concluded that Hibiscus flower extract shows the presence of 15 phytocompounds. The presence of various bioactive compounds justifies the use of the whole flower for various ailments by traditional practitioners.